PERSPEKTIF MAHASISWA TERHADAP FAKTOR NON KOGNITIF PASCA PEMULIHAN PANDEMI COVID-19 - Windyariani, Sistiana; Aa Juhanda; Setiono (LPPM IKIP PGRI Pontianak, 2023)
During the Covid 19 pandemic, there were many changes in learning patterns and habits, both those carried out by lecturers and students. Most lectures were conducted online during the Covid 19 pandemic to avoid the spread of the Covid virus. After the pandemic, courses changed again, namely some offline, some online, and some blended learning. After the Covid-19 pandemic, lecturers needed to know the non-cognitive state of students in adjusting to post-covid-19 recovery conditions. This study aims to analyze the perspective of non-cognitive factors in lectures after recovering from COVID-19. The method used in this research is descriptive with a quantitative approach. The subjects in this study were 69 students from a private university in West Java. Instruments used include questionnaires and interview guidelines. The results showed that students' perceptions of non-cognitive factors after the Covid-19 pandemic had: student motivation in lectures and doing assessments increased after the Covid-19 pandemic; non-cognitive factors that were important for students included motivation, self-confidence, perseverance, tenacity, the concept of self, and anxiety.